Glucose, Cyc8p and Tup1p regulate biofilm formation and dispersal in wild Saccharomyces cerevisiae - Van Nguyen, Phu; Plocek, Vítězslav; Váchová, Libuše; Palková, Zdena (NPJ biofilms and microbiomes, 2020)
Saccharomyces cerevisiae is a mainly beneficial yeast, widely used in the food industry. However, there is growing evidence of its potential pathogenicity, leading to fungemia and invasive infections. The medical impact of yeast pathogens depends on formation of biofilms: multicellular structures, protected from the environment. Cell adhesion is a prerequisite of biofilm formation. We investigated the adherence of wild and genetically modified S. cerevisiae strains, formation of solid-liquid interface biofilms and associated regulation. Planktonic and static cells of wild strain BRF adhered and formed biofilms in glucose-free medium. Tup1p and Cyc8p were key positive and negative regulators, respectively. Glucose caused increased Cyc8p levels and blocked cell adhesion. Even low glucose levels, comparable with levels in the blood, allowed biofilm dispersal and release of planktonic cells. Cyc8p could thus modulate cell adhesion in different niches, dependently on environmental glucose level, e.g., high-glucose blood versus low-glucose tissues in host organisms.
Keywords: biofilmy; kultivační média; Biofilms; Mutation; povrchové vlastnosti; Culture Media; Glucose; regulace genové exprese u hub; represorové proteiny; bakteriální adheze; Saccharomyces cerevisiae Proteins; glukosa; Bacterial Adhesion; Gene Expression Regulation, Fungal; Surface Properties; jaderné proteiny; Nuclear Proteins; Saccharomyces cerevisiae; mutace; Repressor Proteins; Saccharomyces cerevisiae - proteiny